Analysis of the Antimicrobial Stewardship Program Policy on Inpatients Antibiotics Use (Unnes Journal of Public Health, 2022)
The Exploration of Antimicrobial Consumption to Identify Targets for Quality Improvement in Indonesian Hospitals study showed that 97% of the use of empirical antibiotics was 81% empiric therapy, 12% medical prophylaxis, 4% surgical prophylaxis, and 16% without clear indications. The most common diagnoses are typhoid, pneumonia. and dengue fever. The Antimicrobial Stewardship Programme (ASP) Team supports the national program to reduce the use of irrational antibiotics. This study aims to analyse the ASP policy implementation on the use of antibiotics at the Royal Taruma Hospital. A secondary data on the use of Defined Daily Dose (DDD)/100 patient-days for the quarterly months of February, May, and August 2020. The 14 key informants' perceptions, opinions, thoughts are the primary data of qualitative research on the use of antibiotics during the ASP policy implementation. The three most antibiotics used were Ceftriaxone (64.7%), Levofloxacin (20.1%), and Meropenem (6.9%), which belong to the broad-spectrum antibiotic class. The total use of antibiotics was 1206.59 DDD/100 patient-days. The implementation of ASP policies has not been running optimally. It is necessary to formulate a pattern of germs and antimicrobial resistance, not only in the intensive room, but also in the care ward to achieve ASP quality indicators.